Innovations from the “ivory tower”: Wilhelm Barthlott and the paradigm shift in surface science - Neinhuis, Christoph (Beilstein Journal of Nanotechnology, 2017)
This article is mainly about borders that have tremendous influence on our daily life, although many of them exist and act mostly unrecognized. In this article the first objective will be to address more generally the relation between university and society or industry, borders within universities, borders in thinking and the huge amount of misunderstandings and losses resulting from these obvious or hidden borders. In the second part and in more detail, the article will highlight the impact of the research conducted by Wilhelm Barthlott throughout his scientific career during which not only one border was removed, shifted or became more penetrable. Among the various fields of interest not mentioned here (e.g., systematics of Cactaceae, diversity and evolution of epiphytes, the unique natural history of isolated rocky outcrops called inselbergs, or the global distribution of biodiversity), plant surfaces and especially the tremendous diversity of minute structures on leaves, fruits, seeds and other parts of plants represent a common thread through 40 years of scientific career of Wilhelm Barthlott. Based on research that was regarded already old-fashioned in the 1970s and 1980s, systematic botany, results and knowledge were accumulated that, some 20 years later, initiated a fundamental turnover in how surfaces were recognized not only in biology, but even more evident in materials science.
Keywords: Wilhelm Barthlott; 70th birthday; self-cleaning surfaces; lotus-effect

(untitled) - Knoke, T.; Paul, C.; Hildebrandt, P.; Calvas, B.; Castro, L. M.; Härtl, F.; Döllerer, M.; Hamer, U.; Windhorst, D.; Wiersma, Y. F.; Curatola Fernández, G. F.; Obermeier, W. A.; et al. (Nat. Commun., 2016)

(untitled) - Newbold, T.; Hudson, L. N.; Arnell, A. P.; Contu, S.; De Palma, A.; Ferrier, S.; Hill, S. L. L.; Hoskins, A. J.; Lysenko, I.; Phillips, H. R. P.; Burton, V. J.; Chng, C. W. T.; et al. (Science, 2016)

(untitled) - Rauh, W.; Barthlott, W.; Ehler, N. (Bot. Jahrb. Syst. Pflanzengesch. Pflanzengeogr., 1975)

(untitled) - Ehler, N.; Barthlott, W. (Bot. Jahrb. Syst. Pflanzengesch. Pflanzengeogr., 1978)

(untitled) - Barthlott, W.; Voit, G. (Plant Syst. Evol., 1979)

(untitled) - Barthlott, W.; Ziegler, B. (Ber. Dtsch. Bot. Ges., 1980)

(untitled) - Barthlott, W.; Ziegler, B. (Ber. Dtsch. Bot. Ges., 1981)

Current Concepts in Plant Taxonomy - Barthlott, W. (Academic Press, 1984)

(untitled) - Rauh, W.; Schill, R.; Ehler, N.; Barthlott, W. (J. Bromeliad Soc., 1973)

8th World Orchid Conference - Barthlott, W. (German Orchid Society, 1975)

(untitled) - Barthlott, W.; Schultze-Motel, W. (Willdenowia, 1981)

(untitled) - Barthlott, W.; Ehler, N. (Trop. Subtrop. Pflanzenwelt, 1977)

(untitled) - Barthlott, W. (Nord. J. Bot., 1981)

(untitled) - Barthlott, W.; Wollenweber, E. (Trop. Subtrop. Pflanzenwelt, 1981)

(untitled) - Barthlott, W.; Frölich, D. (Plant Syst. Evol., 1983)

(untitled) - Behnke, H.-D.; Barthlott, W. (Nord. J. Bot., 1983)

(untitled) - Engel, T.; Barthlott, W. (Plant Syst. Evol., 1988)

(untitled) - Fehrenbach, S.; Barthlott, W. (Bot. Jahrb. Syst. Pflanzengesch. Pflanzengeogr., 1988)

(untitled) - Frölich, D.; Barthlott, W. (Trop. Subtrop. Pflanzenwelt, 1988)

(untitled) - Barthlott, W. (Evolution and Systematics of the Caryophyllales, 1993)

(untitled) - Ditsch, F.; Barthlott, W. (Trop. Subtrop. Pflanzenwelt, 1994)

(untitled) - Hennig, S.; Barthlott, W.; Meusel, I.; Theisen, I. (Trop. Subtrop. Pflanzenwelt, 1994)

(untitled) - Theisen, I.; Barthlott, W. (Trop. Subtrop. Pflanzenwelt, 1994)

(untitled) - Ditsch, F.; Patha, H.; Barthlott, W. (Beitr. Biol. Pflanz., 1995)

(untitled) - Ditsch, F.; Barthlott, W. (Trop. Subtrop. Pflanzenwelt, 1997)

(untitled) - Wilhelmi, H.; Barthlott, W. (Trop. Subtrop. Pflanzenwelt, 1997)

(untitled) - Barthlott, W.; Neinhuis, C.; Cutler, D.; Ditsch, F.; Meusel, I.; Theisen, I.; Wilhelmi, H. (Bot. J. Linn. Soc., 1998)

The families and genera of vascular plants - Barthlott, W.; Theisen, I. (Springer, 1998)

(untitled) - Meusel, I.; Leistner, E.; Barthlott, W. (Plant Syst. Evol., 1994)

(untitled) - Meusel, I.; Neinhuis, C.; Markstädter, C.; Barthlott, W. (Can. J. Bot., 1999)

(untitled) - Ensikat, H. J.; Neinhuis, C.; Barthlott, W. (Int. J. Plant Sci. (Chicago, IL, U. S.), 2000)

(untitled) - Meusel, I.; Barthlott, W.; Kutzke, H.; Barbier, B. (Powder Diffr., 2000)

(untitled) - Meusel, I.; Neinhuis, C.; Markstädter, C.; Barthlott, W. (Plant Biol., 2000)

Scanning Tunneling Microscopy/Spectroscopy and Related Techniques - Koch, K.; Dommisse, A.; Neinhuis, C.; Barthlott, W. (American Institute of Physics, 2003)

(untitled) - Koch, K.; Barthlott, W.; Koch, S.; Hommes, A.; Wandelt, K.; Mamdouh, W.; De-Feyter, S.; Broekmann, P. (Planta, 2005)

(untitled) - Ensikat, H. J.; Boese, B.; Mader, W.; Barthlott, W.; Koch, K. (Chem. Phys. Lipids, 2006)

(untitled) - Koch, K.; Domisse, A.; Barthlott, W. (Cryst. Growth Des., 2006)

(untitled) - Koch, K.; Dommisse, A.; Niemietz, A.; Barthlott, W.; Wandelt, K. (Surf. Sci., 2009)

Klima- und Umweltforschung an der Universität Bonn - Barthlott, W. (Die Selbstreinigungsfähigkeit pflanzlicher Oberflächen durch Epicuticularwachse, 1992)

(untitled) - Barthlott, W.; Neinhuis, C. (Planta, 1997)

(untitled) - Neinhuis, C.; Barthlott, W. (Ann. Bot. (Oxford, U. K.), 1997)

(untitled) - Barthlott, W.; Neinhuis, C.; Jetter, R.; Bourauel, T.; Riederer, M. (Flora (Jena), 1996)

(untitled) - The Angiosperm Phylogeny Group (Bot. J. Linn. Soc., 2016)

Evolutionsstrategie-Optimierung technischer Systeme nach Prinzipien der biologischen Evolution - Rechenberg, I. (Frommann-Holzboog, 1994)

Evolution and optimum seeking - Schwefel, H. P. (John Wiley & Sons, 1995)

Technical Report No. AFFDL-TR-76-6 - Ishimitsu, K. K.; Van Devender, N.; Dodson, R. O.; Brault, P. C.; Byers, B. A.; Johnson, R. P.; Syring, R. P.; Schaefer, M. P.; Endorf, D. R.; McGinnis, C.; Conley, N. E.; Grant, M. (Boeing Commercial Airplane Company, 1976)

(untitled) - Bechert, D. W.; Bruse, M.; Hage, W. (Exp. Fluids, 2000)

Design in Nature - Mattheck, C. (Springer, 2004)